Crime Scene Characteristics in Rape Cases - Kolarević, Dag (Zbornik Instituta za kriminološka i sociološka istraživanja, 2005)
By using nonmetric multidimensional scaling 1126 solved rape cases (article 103 Criminal Law of Republic of Serbia) has been analyzed. The data were taken from Department of Informatics of Ministry of Interior affairs of republic of Serbia and were collected from Serbia and Vojvodina from 1991. to 2001. Elementary crime scene characteristics have been analyzed and those were location type, weapons, method of approach, method of attack, method of arriving and opportunistic elements. Set of nominal variables was transformed to binary form and analyzed by "alscal" technique. In accordance with earlier researches it has been chosen twodimensional solution. Stress value 0.157 was acceptable. Examination of visual plot made it possible to divide rapist in two groups, based on crime scene characteristics. First group consisted of rapists who use indoor locations such as flat, public or working place, who use weapons or physical force, sex invitation or blitz approach. They tend to exploit victim's weakness or helplessness, they use vehicles in arriving to the crime scene and they choose certain locations or time as opportunistic elements. Second groups consisted of rapist who uses threat in outdoor locations, confident approach, they arriving bye foot and exploit some victim's features such as ignorance or thrust. In the end, results were brought in connection with earlier theoretical findings.